Managing Variant Interpretation Discrepancies in Hereditary Cancer: Clinical Practice, Concerns, and Desired Resources. Issue 4 (20th December 2017) - Zirkelbach, Ellen; Hashmi, Syed; Ramdaney, Aarti; Dunnington, Leslie; Ashfaq, Myla; Nugent, Elizabeth K.; Wilson, Kate
Abstract: Variant interpretation is a complex process, and classification may vary between sources. This study aimed to determine the practice of cancer genetic counselors regarding discrepancies in variant interpretation and to identify concerns when counseling these discrepancies. An electronic survey was sent to genetic counselors in the NSGC Cancer Special Interest Group. The vast majority of counselors (93%) had seen a variant interpretation discrepancy in practice. A large majority (96%) of respondents indicated that they conducted their own research on reported variants. Most respondents cited variant databases as the most common resource utilized in researching variants. Approximately 33% of counselors spent 45 min or more of extra time researching a discrepancy compared to researching a variant with a single classification. When asked how they approached counseling sessions involving variant interpretation discrepancies, the free responses emphasized that counselors considered family history, clinical information, and psychosocial concerns, showing that genetic counselors tailored the session to each individual. Discrepancies in variant interpretation are an ongoing concern for clinical cancer genetic counselors, as demonstrated by the fact that counselors desired further resources to aid in addressing these discrepancies, including a centralized database (89%), guidelines from a major organization (88%), continuing education about the issue (74%), and functional studies (58%). Additionally, most respondents reported that the ideal database would be owned by a non‐profit organization (59%) and obtain information directly from laboratories (91%). This investigation was the first to address these discrepancies from a clinical point of view. The study demonstrates that discrepancies in variant interpretation are a concern for clinical cancer genetic counselors and outlines the need for additional support.